The mediatory role of challenge and threat in the relationship between positive thinking skills and perception of excellent performance: a study on football players - Pepe, O.; Koc, M. C.; Ayhan, C.; Talaghir, L.-G.; Bentea, C.-C. (Frontiers in Psychology, 2025)
Purpose: The present study aims to examine the mediating role of challenge and threat between positive thinking skills and perception of excellent performance in football players competing in the regional amateur league, which is referred to as a semi-professional league in Turkey.